MM-398 Plus 5-FU and LV Extend OS and PFS in mPAC - Nichols, Emma Hitt (MD Conference Express, 2014)
The addition of MM-398 to 5-flurouracil (5-FU) and leucovorin (LV) extended overall survival and progression-free survival in patients with metastatic pancreatic adenocarcinoma who had previously received gemcitabine-based treatment when compared with 5-FU plus LV alone. This article presents data from the Study of MM-398 With or Without 5-Fluorouracil and Leucovorin, Versus 5-Fluorouracil and Leucovorin in Patients With Metastatic Pancreatic Cancer [NAPOLI 1; Von Hoff D et al. Ann Oncol. 2014 (abstr O-0003)].